The importance of Georgia's resort and recreational resources and geographical classification of resorts - Elizbarashvili, Nodar; Svanadze, David; Elizbarashvili, Rusudan; Gurgenidze, Miranda; Bubashvili, Luiza (Human Geography Journal, 2025)
The article discusses the geographical features and classification of Georgia's resort and recreational resources. Recreation and recreational farming are related to the geographical environment, its natural characteristics and landscape diversity, and the geographical features of farming and social infrastructure.The field of study of recreational geography includes those objects that consist of natural and social elements. Due to this, it has developed on the border of separate directions of both natural and social geography, medical geography and geography.Geographical research of resorts, as well as recreational facilities, can be carried out using both geographical analysis and synthesis, as well as comparative, expeditionary, geoinformatics, sociological, and other methods.For geographical research of resorts and resort economy, it is desirable to study such issues as:The impact of the natural environment or landscape on human health;Landscape structure and functions;Research on the recreational (resort) and aesthetic value of the landscape;Classification of resorts according to location, landscapes, purpose (treatment of diseases), mineral or thermal waters, climate (dryness index, sunlight, temperature amplitude, pressure, humidity, snow cover), natural resource potential (vegetation, reservoirs, fauna, natural monuments, relief, etc.), usage traditions (i.e. history), folk beliefs (attitude of the local population to medicine), uniqueness, historical-cultural (historical monuments, cultural objects, etc.) and transport (accessibility, Internet, etc.) infrastructure, and in general - natural and socio-economic factors;A complex assessment of recreational potential involves the study of dozens of issues and objects, which is a rather difficult scientific and practical task.  There are no generally accepted criteria for it, which makes it difficult to make a complex assessment of natural, historical-cultural, or socio-economic factors.Georgia is distinguished throughout the world, and especially in the Caucasus, by its recreational resources. There are more than 100 resorts and resort areas in Georgia. About 2 thousand mineral springs have been identified and studied, most of which are distinguished by their high balneological purpose. Georgia has all types of resorts known worldwide. The main ones are sea, mountain, and climatic-balneological resorts.The article discusses the geographical, historical-cultural, recreational and infrastructural features of 55 Georgian resorts. A total of 29 parameters were considered, 25 of which are not found in the scientific literature related to Georgian resortology.